High-quality reference transcriptome construction improves RNA-seq quantification in Oryza sativa indica - Srikakulam, Nagesh; Sridevi, Ganapathi; Pandi, Gopal (Frontiers in Genetics, 2022)
Reference Transcriptomic Dataset (RTD) is an accurate and comprehensive collection of the transcripts originated in a given organism. It holds the key for accurate transcript quantifications and downstream analysis of differentially expressions and regulations. Currently, transcriptome annotations for most crop plants are far from complete. Oryza sativa indica (O. sativa indica) has been reported to have 40,759 transcripts in Ensembl database without alternative transcript isoforms and alternative splicing (AS) events. In order to generate a high-quality IndicaRTD, RNA sequencing was carried out on 18 samples under various time points. The obtained reads were analyzed by adopting the recently developed computational analysis pipeline to assemble the RTD with increased transcript and AS diversity for O. sativa indica (IndicaRTD). The new assembled transcriptome annotation comprises of 122,968 non-redundant transcripts from 53,695 genes after stringent quality filtering. Current study identifies a large number of novel transcripts compares to the Ensembl deposited data that are important for the regulation of molecular and physiological process in the plant system. Currently, assembled IndicaRTD must allow fast quantifications of transcript and gene expressions with high precision.